2017
DOI: 10.1111/aab.12405
|View full text |Cite
|
Sign up to set email alerts
|

Seed vigour contributes to yield improvement in dry direct‐seeded rainfed lowland rice

Abstract: Dry direct-seeded rice (DSR) cultivation is widely spreading in tropical Asia, but drought and nutrient deficiency stresses often cause crop failure in rainfed lowlands. The objective of this study was to dissect the physio-morphological characteristics associated with crop establishment and early vigour of DSR under drought and P deficiency conditions in the Philippines. It was found that new drought-resistant cultivars bred for DSR (Rc348 and Rc192) had faster germination and sprout growth than popular irrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…It demonstrates that the plants adapt to different mechanisms to survive and reproduce under various abiotic stresses. Rice cultivars were evaluated at two different locations in glass house and field conditions to dissect the physio-morphological characteristics associated with crop establishment and early vigour of direct seeded rice under drought and P deficiency conditions and found that quick germination and seedling vigour with quick root anchorage and great nutrient uptake capacity, are the important traits for moisture and nutrients stress conditions 61 . A significant interaction between genotype and water regime was observed for plant height and primary root number.…”
Section: Discussionmentioning
confidence: 99%
“…It demonstrates that the plants adapt to different mechanisms to survive and reproduce under various abiotic stresses. Rice cultivars were evaluated at two different locations in glass house and field conditions to dissect the physio-morphological characteristics associated with crop establishment and early vigour of direct seeded rice under drought and P deficiency conditions and found that quick germination and seedling vigour with quick root anchorage and great nutrient uptake capacity, are the important traits for moisture and nutrients stress conditions 61 . A significant interaction between genotype and water regime was observed for plant height and primary root number.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true in the early stage of rice growth, which is easily affected by climate, weeds, and other factors 15 , 16 . In view of the climate and weed problems faced by dry direct-seeded rice cultivation, experts have researched several variations, such as improving rice varieties 17 , adjusting agronomic parameters 18 , 19 , and film-covering seeding 20 . Film-covering seeding has proven to be one of the most effective solutions.…”
Section: Introductionmentioning
confidence: 99%
“…This trend has driven most rice farmers to shift from transplanting seedlings to dry direct-seeding. However, the poor crop establishment and inefficient weed control in this approach often constrain yields (Kumar & Ladha, 2011;Yamane et al, 2018). Furthermore, severe pest outbreaks have become more frequent in direct-seeded rice fields, owing in part to ongoing climate change (Ali et al, 2014;Jairin et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%